Analisis program sanitasi total berbasis masyarakat (STBM) pilar cuci tangan pakai sabun pada anak SD - Imran Matondang (Jurnal SAGO Gizi dan Kesehatan, 2021)
Background: The problem of washing hands with soap in elementary school students is still high. Elementary schools in Kuala Pesisir Subdistrict, Nagan Raya Regency have not implemented hand washing with soap according to the 6-step principle. Efforts made by the Health Office to make this program successful are by increasing student compliance in hand washing activities through socialization and direct practice.Objective: This study aims to analyze the factors that influence the success of the pilar community-based total sanitation program for washing hands with soap at elementary school levels class V and VI in Kuala Pesisir District, Nagan Raya Regency.Method: Design This research is a cross sectional study. Data were collected using a questionnaire with a sample size of 240 students consisting of grades V and VI. Statistical analysis using Chi-square test and Binary Logistics Regression.Results: The results of bivariate analysis showed that there was a relationship between knowledge (p=0.002), attitude (p=0.007), behavior p=(0.000), hand washing facilities (p=0.000), teacher support (p=0.036), and availability of water (p=0.036). p=0.000) with a total community-based sanitation program pillar washing hands with soap. Based on multivariate analysis, the dominant variables associated with the pillars of hand washing with soap are behavior (OR=0.207; 95%CI: 0.082-0.524), water availability (OR=0.173; 95%CI: 0.050-0.595) and facilities. wash hands (OR=0.153; 95%CI: 0.047-0.501).Conclusion: It was concluded that positive student behavior 0.207 times was associated with the success of the hand washing program with soap compared to negative student behavior.